(untitled) (Bangladesh Journal of Pharmacology, 2013)
Urinary bladder cancer is one of the most commonly diagnosed urological malignancies worldwide. Dracorhodin perchlorate, anthocyanin red pigment, has been recently shown to induce apoptotic cell death in several types of cancer cells. However, there is no report elucidating its effect on bladder cancer T24 cells. In this study, for the first time, we investigated the effects of dracorhodin perchlorate on the cell viability and apoptosis in human bladder cancer T24 cells. DNA flow cytometric analysis demonstrated that dracorhodin perchlorate markedly rendered apoptosis of T24 cells in a time-dependent manner. Dracorhodin perchlorate significantly induced the dissipation of mitochondrial membrane potential in T24 cells. Furthermore, dracor-hodin perchlorate-induced apoptosis was regulated by activation of caspase-3 and down-regulation of antiapoptotic proteins, Bcl-2, Bcl-XL, and survivin in T24 cells. These in vitro results suggested that dracorhodin perchlorate should be further examined for in vivo activity and molecular mechanism in human bladder cancer.